2021
DOI: 10.1186/s40364-021-00302-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower BCL11B expression is associated with adverse clinical outcome for patients with myelodysplastic syndrome

Abstract: Myelodysplastic syndrome (MDS) is an aggressive and genetically heterogeneous disease with poor prognosis. Cellular immune disorder is a common characteristic of this disease and is thought to be related to clinical outcome. Alterations in T cell clonal expansion and T cell dysfunction has been detected in MDS patients. Little is known about whether there are immune biomarkers to evaluate the T cell alterations with clinical outcome. Previous studies have demonstrated that B-cell leukemia/lymphoma 11B (BCL11B)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…BCL11B was identified as an important role in T-cell function [ 34 ], and its lower expression is associated with adverse clinical outcomes for patients with myelodysplastic syndrome [ 36 ]. DUSP2 can control the activity of the transcription activator signal transducer and the activator of transcription 3 in its regulation of TH17 differentiation [ 37 ], and can also act as an immune checkpoint in T-cell antitumor immunity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…BCL11B was identified as an important role in T-cell function [ 34 ], and its lower expression is associated with adverse clinical outcomes for patients with myelodysplastic syndrome [ 36 ]. DUSP2 can control the activity of the transcription activator signal transducer and the activator of transcription 3 in its regulation of TH17 differentiation [ 37 ], and can also act as an immune checkpoint in T-cell antitumor immunity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, eleven CMs were analyzed, and seven were associated with the prognosis of TCM patients. However, different hematological malignancies may have different immune receptor abnormalities, and the combination of two related immune receptors has greater advantages compared with a single molecule in predicting the prognosis of patients [ 5 , 6 , 8 , 11 ]. Interestingly, CD5 had the strongest correlation with CD6, and low expression of CD5 and CD6 was significantly associated with adverse outcomes in TCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TCL accounts for approximately 2% of non-Hodgkin's lymphoma and has a poor prognosis compared with B-cell lymphoma [4]. Gene mutations and abnormal expression are often used as prognostic biomarkers for risk strati cation of cancer patients [5][6][7]. Recently, abnormal expressions of costimulatory and inhibitory molecules were also used as prognostic biomarkers for hematological malignancies [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…TCF1+ tumor-infiltrating lymphocytes (TILs) have been positively correlated with tumor regression, successful response to anti-PD-1 treatment, and longer overall survival (OS) (27,28). Multiple studies have also found that decreased BCL11B expression predicts inferior clinical outcome in adult standard risk T cell acute lymphoblastic leukemia and myelodysplastic syndrome (29,30). However, the effects of TCF1 and BCL11B expression on the prognosis of CLL patients remain unclear.…”
Section: Introductionmentioning
confidence: 99%